Penerapan Strategi Pengelolaan Keuangan Berbasis Excel Bagi Pelaku UMKM Sempol Ayam Jooz Di Kota Bekasi Untuk Meningkatkan Keberlanjutan Bisnis - Delima, Adinda Asri; Rohalia, Gita; Kurnia, Ramdhan Dwi; Lestari, Winda Puji; Pupung purnamasari (CV. ITTC INDONESIA, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, especially the culinary sector, have great potential but are often hampered by inadequate financial management. Thi s research seeks to improve the sustainability of the Sempol Ayam Jooz MSME business in Bekasi City through the implementation of a Microsoft Excel-based financial management strategy. Qualitative methods are used with an approach of interviews, observations, and direct training to owners and employees. The results show that the previous manual financial recording system was ineffective. This research developed an Excel template to record daily transactions, sales, and provide a financial dashboard. Intensive training and mentoring are provided to ensure proper understanding and implementation. The application of Excel templates has been proven to provide practical solutions, increase operational efficiency, and support better business decision-making, thereby contributing to the sustainability of Sempol Ayam Jooz MSME business.